Strategies for Passing UKOM Exit Exam for Nurse Profession Program in AIPNI Region XIII - Syariefah Hidayati Waliulu; Ratna Sari Rumakey (Humanistic Network for Science and Technology (HNST), 2022)
The passing rate for the Nurse Competency Test in the AIPNI Regional XIII is still relatively low compared to other provinces. Institutions have an essential role in preparing students to participate in the Competency Test (UKOM) so that universities can take various strategies to improve the ability of their students to face the test. The purpose of this study was to obtain an overview of the institutional strategies to increase the passing rate of the UKOM exit exam for nurse profession students. This study was qualitative research conducted through in-depth interviews at each institution in the AIPNI Region XIII, including STIKes Maluku Husada, STIKes Pasapua, STIKes Papua, STIKes Jayapura, PSIK Cendrawasih University, and STIKes Halmahera. The study's results describe three aspects of the strategy: lecturers, students, and institutions. From the three aspects, it can be concluded that not all lecturers have attended preceptorship training and item development of UKOM question writing, some institutions already have CBT, students participate in campus and off-campus guidance activities, and students must follow several institutional policies before joining UKOM. Keywords: UKOM; nurse profession; exit exam